Empowerment for MSMEs in Supporting the Borobudur National Tourism Strategic Area in Wringinputih Village, Borobudur District Through Marketing Digitalization: Pemberdayaan bagi UMKM dalam mendukung Kawasan Strategis Pariwisata Nasional (KSPN) Borobudur di Desa Wringinputih, Kecamatan Borobudur Melalui Digitalisasi Pemasaran - Muhdiyanto, M; Yuliani, Nur Laila; Darmadi, Ravindra Ardiana (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Wringinputih Village is a village located in Borobudur District, Magelang Regency and is one of the places that supports tourism in Borobudur District thanks to the emergence of the Guyub Rukun Village-Owned Enterprise (BUMDes) which provides several rides that can be visited by visiting tourists. Apart from the several business units available, BUMDes Guyub Rukun is also expanding their reach towards education to MSMEs to improve village welfare, support and increase tourist destinations in the Borobudur National Tourism Strategic Area (KSPN). SMEs fostered by BUMDes Guyup Rukun include Jet Kolet SMEs, Screen Printing SMEs, and Jammu SMEs. However, there are still several shortcomings related to marketing in MSMEs, such as not having a brand name and marketing channels that are narrow and have not been digitized. After training and mentoring shows, partners are able to make attractive branding and packaging. Furthermore, related to marketing digitization partners are able to implement marketing digitalization, such as websites, Instagram and Facebook.